2019
DOI: 10.1097/md.0000000000014710
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effectiveness between complete internal limiting membrane peeling and internal limiting membrane peeling with preservation of the central fovea in combination with 25G vitrectomy for the treatment of high myopic foveoschisis

Abstract: Vitrectomy combined with internal limiting membrane peeling (ILMP) treats high myopic foveoschisis with good results, but there is a risk of iatrogenic macular holes, which may be reduced by preserving the internal limiting membrane of the central fovea. This study compared complete ILMP with partial ILMP, both combined with 25G vitrectomy, for the treatment of high myopic foveoschisis.Thirty-three cases (33 eyes) of high myopic foveoschisis were retrospectively analyzed. They underwent 25G vitrectomy combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…In addition, postoperative VA was superior in eyes with fovea-sparing ILM peeling. Similar results have been reported in two other studies (24,25), however, a recent study has argued that there was no difference in the postoperative VA between fovea-sparing and complete ILM peeling groups and that the rate of postoperative MH development was not significant (2/20 vs. 0/13; p = 0.508) (26). The potential benefit of fovea-sparing ILM peeling compared to complete ILM peeling has not been established yet and this needs to be addressed in the future.…”
Section: Myopic Choroidal Neovascularization (Cnv)supporting
confidence: 88%
“…In addition, postoperative VA was superior in eyes with fovea-sparing ILM peeling. Similar results have been reported in two other studies (24,25), however, a recent study has argued that there was no difference in the postoperative VA between fovea-sparing and complete ILM peeling groups and that the rate of postoperative MH development was not significant (2/20 vs. 0/13; p = 0.508) (26). The potential benefit of fovea-sparing ILM peeling compared to complete ILM peeling has not been established yet and this needs to be addressed in the future.…”
Section: Myopic Choroidal Neovascularization (Cnv)supporting
confidence: 88%
“…Such adverse events may be even more common in pathological myopia, characterized by long axial length and diffuse chorioretinal atrophy. To prevent postoperative macular hole formation and possible damage to the fovea, a fovea-sparing ILMP technique has been advocated [8,19,20], but some studies have shown that there is no difference in postoperative visual acuity between fovea-sparing ILMP and complete ILMP [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Many subsequent studies have demonstrated that vitrectomy with internal limiting membrane peeling (ILMP) can be effective in producing both anatomical and functional improvement in MF [3][4][5][6][7]. In order to reduce postoperative macular hole (MH) formation and foveal damage, a partial ILMP technique with foveal sparing was proposed [8], but there is little evidence that this technique has better outcomes than complete ILMP [9,10] Furthermore, more recent studies have shown similar anatomical and functional improvements can be achieved without any form of IMLP [4,11], casting doubt on the benefits of ILMP.…”
Section: Introductionmentioning
confidence: 99%
“…[39,43] The reported incidence of foveoschisis in high myopia is 9-34%, and approximately 50% of patients with foveoschisis will subsequently develop either a MH or retinal detachment within 2 years. [44] Mean age for MMH formation is 55 years. [43] In a study evaluating the severity of myopia as a risk factor for MH development, longer axial length and higher myopia were found to correlate with younger age of MH onset (P < 0.0001 for both).…”
Section: Myopic Mhs (Mmhs)mentioning
confidence: 99%
“…Another recent retrospective study also compared ILM peeling with foveolar sparing ILM peeling during vitrectomy surgery with gas tamponade for myopic foveoschisis without MH. [44] Twenty eyes underwent traditional ILM peeing and 13 eyes underwent foveolar sparing ILM peeling. Full regression of foveoschisis was observed in 75% and 77% of eyes in traditional ILM peeling and foveal sparing groups, respectively.…”
Section: Ilm Peeling Inverted Ilm Flap and Foveolar Sparing Ilm Peelingmentioning
confidence: 99%